Eccrine sweat glands associate with the human hair follicle within a defined compartment of dermal white adipose tissue3. (30th March 2018) - Poblet, E.; Jimenez, F.; Escario‐Travesedo, E.; Hardman, J.A.; Hernández‐Hernández, I.; Agudo‐Mena, J.L.; Cabrera‐Galvan, J.J.; Nicu, C.; Paus, R.
Summary: Background: Eccrine sweat glands (ESGs) are critical for thermoregulation and are involved in wound healing. ESGs have traditionally been considered as separate skin appendages without connection to the pilosebaceous unit (PSU). However, recent preliminary evidence has encouraged the hypothesis that the PSU and ESG are more interconnected than previously thought. Objectives: To re‐evaluate the morphology of human skin adnexa with an integrated three‐dimensional (3D) perspective in order to explore the possible interconnections that the PSU and the ESG may form. Methods: A systematic 3D reconstruction method of skin sections, direct visualization of human scalp follicular unit transplant grafts and a scalp strip ex vivo were used to validate and further explore the hypothesis. Results: We demonstrate that the coiled portion of most ESGs is morphologically integrated into the PSU of human scalp skin and forms a structural unit that is embedded into a specific, hair follicle‐associated region of dermal white adipose tissue (dWAT). This newly recognized unit is easily accessible and experimentally tractable by organ culture of follicular units and can be visualized intravitally. Conclusions: We propose a model of functional human skin anatomy in which ESGs are closely associated with the PSU and the dWAT to form a common homeostatic tissue environment, which may best be encapsulated in the term 'adnexal skin unit'. The challenge now is to dissect how each component of this superstructure of human skin functionally cooperates with and influences the other under physiological conditions, during regeneration and repair and in selected skin diseases. Abstract : What's already known about this topic? Eccrine sweat glands (ESGs) are traditionally regarded as being separate from the pilosebaceous unit (PSU). However, it has recently been hypothesized that human scalp ESGs may actually form an integral part of the PSU. The dermal white adipose tissue (dWAT), formally called the upper subcutis, is known to differ functionally from subcutaneous adipocytes and to be associated with hair follicles. What does this study add? We show by three‐dimensional reconstruction imaging and intravital dye staining that the coiled portion of scalp ESGs is morphologically closely associated with neighbouring hair follicles and that both form a structural adnexal skin unit that is largely embedded into the dWAT. The location of the ESG coil can be identified macroscopically in a distinct area, close to the connective tissue sheath of the hair follicles, right below the sebaceous gland. What is the translational message? The described observation is clinically relevant as it mandates to evaluate and consider individual skin appendage structures and their embedding into the dWAT as one morphological unit of human skin. In this unit, each element may influence the other under physiological conditions, during wound healing and in selected skin diseases. Pharmacological manipulation of one component of the unit may therapeutically impact on another. Plain language summary available online Respond to this article